Karakteristik Arsitektur di Wilayah Budaya Betawi Ora - Bachtiar Firmansyah (MARKA (Media Arsitektur dan Kota) : Jurnal Ilmiah Penelitian, 2018)
Migration was one of the reason that make Betawi ethnic, indigineous people who lived in Batavia, become minority in its homeland. Most of the Betawi people live in suburb area, and it expands the scope of Betawi cultural area until Bekasi, Tangerang. Depok and even part of Karawang. The Betawi culture on the periphery area (Betawi Udik/Ora) has different characteristics, due to the influence of Sundanese and Betawi culture that are geographically close together. This is also reflected in the form of local architecture which often affected by those two cultures. Observations were made on several traditional houses in Cikarang and Pebayuran area, Bekasi Regency to find out the typology that emerged and its relation to Sundanese and Betawi architecture.